PENGARUH GAYA KEPEMIMPINAN, DAN BUDAYA ORGANISASI, TERHADAP KINERJA KARYAWAN MELALUI VARIABLE INTERVENING STRESS KERJA PADA PT. MUTIARA LAUT ABADI MEDAN - Anton, Anton; Karo-karo, Alex P.; Tjendana, Martinus (Jurnal Manajemen dan Bisnis, 2023)
This study examines the influence of leadership style and organizational culture on employee performance through work stress intervening variables. By taking a sample of 130 people from a population of 191 people. Analyzed using path analysis with SPSS. The results show that work stress negatively affects leadership style and organizational culture on employee performance, meaning that the better the leadership style and organizational culture, the lower employee stress levels will increase employee performance.